SELF REGULATED LEARNING DALAM PERKULIAHAN TARJAMAH INDONESIA-ARAB MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA ARAB UNNES - Akbar Syamsul Arifin; Nafis Azmi Amrullah; Hasan Busri (Universitas Negeri Semarang, 2022)
This study examines the application of the self-regulated learning method in improving the ability of students of the Unnes Arabic education study program in translating Indonesian texts into Arabic. Indonesian-Arabic translation skills require many other supporting abilities, such as knowledge of grammar, semantics, and cultural insight both used in the source language and also the target language. Therefore, a separate method is needed that allows students to examine many aspects of this knowledge to be able to translate Indonesian-Arabic texts. The method is self-regulated learning which is able to increase student motivation in learning, self-regulation, time and learning methods to achieve learning goals as well as reflecting and evaluating the activities and learning outcomes that are applied. The research subjects in this study were Arabic students of the Unnes Arabic Language Education study program semester VI who took the Indonesian-Arabic Tarjamah course, Big Class B. This research took place from March-June 2021. The results of this study showed the application of the self-regulated learning method in Indonesian-Arabic tarjamah lectures, are able to increase motivation and ability to translate Indonesian-Arabic which can be seen from the final grades of students with a presentation of 5 (20%) students graduating with an A grade (86-87). 19 (76%) students got AB scores (81-85), and 1 (4%) students got B grades (78).